HUBUNGAN PENGETAHUAN MENGENAI COVID-19 DENGAN TINGKAT STRES PADA SISWA SMK NEGERI 1 MODOINDING - Batas, Novia (Journal Of Community & Emergency, 2024)
ABSTRACT The current COVID-19 virus pandemic has an impact on changing aspects of life, including causing stress. Stress can attack anyone, including students. Lack of knowledge is one of the factors that causes stress in students. The aim is to find out the relationship between knowledge about Covid-19 and stress levels in SMK Negeri 1 Modoinding students. This research uses a cross sectional study, namely research data can be collected according to the conditions when the research is taking place, so that data collection is enough to be done once or at the time the research is carried out. The population of 37 students with a sample using the totaling population obtained 39 students. Data analysis used the chi-squared test with a significance level of 95% (α): 0.05. The results of the respondents' knowledge were mostly in the unfavorable category, which amounted to 24 respondents or 64.9%, while the unfavorable category was 13 people or 35.1%. At the level of stress, severe stress is the most common category in this study, which amounted to 22 respondents or 59.5% and respondents who were in the mild category were 15 respondents or 40.5%. Based on the results of statistical tests using the chi square test, the value of -value = 0.000 is smaller than the value of = 0.05. It means that H0 is rejected, then there is a relationship between knowledge about Covid-19 and the level of stress in SMK Negeri 1 Modoinding students. There is a relationship between knowledge about Covid-19 and stress levels in SMK Negeri 1 Modoinding students